2014
DOI: 10.1039/c4en00052h
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of nanoceria in biologically-relevant environments

Abstract: Cerium oxide nanoparticles (nanoceria) have gained considerable attention in biological research due to their anti-oxidant like behaviour and regenerative nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 93 publications
0
90
0
Order By: Relevance
“…In short, they noted that a minor modification in the synthesis route may have a major impact on the biological activity and toxicity of ceria and pointed out that reproducibility in nanomaterials synthesis often constitutes a challenge. Kumar et al [32] also discussed many gaps that need to be filled with regard to nanoceria toxicity. For example, a better understanding of the influence of the precursor's purity, nanoceria morphology, binding sites, and long-term biotransformation in vivo is still strongly needed.…”
Section: Toxicity Of Nanoceriamentioning
confidence: 99%
See 2 more Smart Citations
“…In short, they noted that a minor modification in the synthesis route may have a major impact on the biological activity and toxicity of ceria and pointed out that reproducibility in nanomaterials synthesis often constitutes a challenge. Kumar et al [32] also discussed many gaps that need to be filled with regard to nanoceria toxicity. For example, a better understanding of the influence of the precursor's purity, nanoceria morphology, binding sites, and long-term biotransformation in vivo is still strongly needed.…”
Section: Toxicity Of Nanoceriamentioning
confidence: 99%
“…[31] The lower toxicity with smaller ceria particle size can also be explained by the higher tendency of smaller NPs to form agglomerates. [32] It is also well known that the surface properties, such as the zeta potential, of NPs play a key role in their biocompatibility. [33] The zeta potential of particles can be modified by changing, for example, the pH of the solution [34] or by using a coating.…”
Section: Toxicity Of Nanoceriamentioning
confidence: 99%
See 1 more Smart Citation
“…16 In vivo studies revealed that nanoceria fights against inflammation, ischemic stroke and radiation-induced damages. 11,17 With so many biological applications, however, few studies touched upon its interaction with biological molecules, 18 especially biomembranes. 10,16 To enter cells, nanoceria has to first cross the cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Strobel et al have found that endothelial cells have the ability to clear up the nanoceria through a process called exocytosis which helps to reduce the adverse effect of it [62]. But as the use of different types of nanoceria are still in developing stage more research needs to be done about the fate, transformation, transport, toxicity, the interaction of nanoceria [63]. …”
Section: Recent Trends and Future Perspectivementioning
confidence: 99%